Microbial bioremediation and biodegradation of hydrocarbons, heavy metals, and radioactive wastes in solids and wastewaters - Kumar R.; Kundu S. (My University, 2025)
In this era of rapid industrialization, there is an increase in humongous use of nonrenewable resources which generate wastes in terms of hydrocarbons, heavy metals, and radioactive wastes. Increase in the wastes generated is a great threat to the environment as well as human life. The hydrocarbon industry, mining industry, and increase in the use of radioactive sources of energy created enormous toxic heaps, which are not degradable for years to come. No novel technology has been developed to rapidly tackle these critical masses of toxic wastes. Underground dumping and deep-sea disposal are the only treatment methods are being carried out. The great marine oil spill in the Mexican Gulf and wastes of nuclear warheads are a critical threat to humankind. The primary focus of the chapter is the treatment of these wastes through different biological processes and routes.Ahuge number of treatment studies on differentwastes utilizaing biological methods are being done. Less heed is given to wastes such as hydrocarbon wastes, heavy metals, and more specifically radioactive wastes. Major challenges in the treatment of these wastes are that they have slower rate of degradation and handling of these kinds of wastes becomes a major roadblock. Chemolithotrophs and chemoorganotrophs are the major microorganisms which utilize chemical energy for their functioning. Facultative anaerobes and obligate anaerobes are known for their high COD treatment efficiency which is highly effective in treatment of such category of wastes. This chapter focuses on the use of these microorganisms for the treatment of the three main kinds of wastes, i.e., hydrocarbons, heavy metals, and radioactive wastes from solids and wastewaters. © Springer Nature Singapore Pte Ltd. 2020.